A Persepsi Siswa Terhadap Guru Bahasa Inggris Ideal di Era Digital Berdasarkan Teori Baruch di SMA Negeri 4 Lubuklinggau: STUDENTS’ PERCEPTION OF IDEAL ENGLISH TEACHERS IN THE DIGITAL ERA BASED ON BARUCH THEORY AT SMA NEGERI 4 LUBUKLINGGAU - hendra, nur_azizulfikri (Lingustic, Literature and English Education, 2024)
This research aimed to identify and describe the students' perceptions of ideal English teachers in the digital era based on Baruch theory at SMA Negeri 4 Lubuklinggau. The method in this research was descriptive qualitative. The population were the eleventh and the twelfth graders of SMA Negeri 4 Lubuklinggau. In choosing the sample, two stages namely stratified and simple random sampling were used. The result of the samples were XI.4, XI.5, XII.1, and XII.2, with each class represented by 10 students. The data were collected by using quesionaire. Furthermore, the data were analyzed with Baruch Theory in the form of statement. The result showed that an ideal English teacher from both professional and personal perspectives. Professionally, students emphasized the importance of teachers who use varied and engaging teaching methods, integrate technology effectively, maintain consistency and fairness, and demonstrate strong classroom management. On a personal, students valued teachers who are friendly, patient, good listeners, morally upright, and have a sense of humor. The findings suggest that students at SMA Negeri 4 Lubuklinggau perceive the ideal English teacher as one who is both professionally competent and personally approachable. It can be concluded that they seek teachers who are not only knowledgeable and innovative but also empathetic and supportive, highlighting the evolving needs of students for a balanced approach to education.